Escaping the Captive Market: Strategic Innovation in Co-branding and Mitigating Community-induced Inefficiencies in Faith-Based Micro-Enterprises - Abdulloh Azzahid; Mohamad Rizan; Saparuddin Mukhtar (Journal of Strategic Innovation in Economics and Business, 2026)
This study evaluates the effectiveness of marketing strategies in religious-based business entities in developing countries, with a particular focus on Islamic boarding schools in Indonesia that receive government capital assistance. Using the Structural Equation Modeling (SEM-PLS) model on a sample of 230 business units, this study examines how co-branding and distribution channel management strategies affect marketing performance, both directly and through community marketing mediation. Empirical results show findings that contradict conventional wisdom: although co-branding strategies are proven to significantly improve performance (β=0.208), distribution channel management (β=-0.134) and community marketing (β=-0.217) are negatively correlated with marketing performance. Furthermore, community marketing was found to negatively mediate the relationship between co-branding, indicating the existence of “social costs” and “network exclusivity” phenomena that burden business efficiency. These findings provide important theoretical contributions regarding the limitations of bonding social capital in religious entrepreneurship, suggesting that over-reliance on internal communities and traditional distribution channels without digitalization support can hinder commercial growth.